Determinants of Employee Performance at the Teluk Dalam District Office, Simeulue Regency - Putra, Ardi Wansyah; Rahmi, Amelia; Safitri , Husnaina Mailsa (Scimadly Publishing, 2025)
This study aims to analyze the influence of internal communication, work quality, and workplace spirituality on employee performance at the Teluk Dalam District Office, Simeulue Regency. Using a quantitative causal design, data were collected from 32 employees through questionnaires and analyzed using multiple linear regression with SPSS 26. The results show that internal communication, work quality, and spirituality have a positive and significant effect on employee performance, with spirituality emerging as the most dominant factor. The model explains 70.2% of the variation in performance, confirming the crucial role of intrinsic motivation and moral values in public service. Theoretically, the study contributes to human capital and workplace spirituality literature by integrating spiritual dimensions into performance models for public organizations. From a policy perspective, the findings suggest that local governments should enhance communication systems, strengthen employee development, and institutionalize spiritual and ethical programs to improve service quality. However, the limited sample size and cross-sectional design restrict the generalizability of findings. Future research should include broader samples and longitudinal designs to deepen theoretical and practical insights.